Systems of one-dimensional subspaces of a Hilbert space - Samoilenko, Yu. S.; Grushevoi, R. V. (Methods of Functional Analysis and Topology, 2010)
We study systems of one-dimensional subspaces of a Hilbert space. For such systems, symmetric and orthoscalar systems, as well as graph related configurations of one-dimensional subspaces have been studied.